Dead dog road: a true story into the dark world of an abused child - Black, Diane N. (Black Flower Press, 2024)
"In a small Texas town, the director of a children's home tries to save three adopted Russian children living with a sadistic woman in the backwoods of Caney Head. A heart-stopping story that highlights the failure of the agencies we trust to protect the most vulnerable among us--and a truth more compelling and powerful than we could imagine. Abuse reports from neighbors draw attention to twelve-year-old Alexey who runs away to hide in the woods. The local child protection agency sends the director of the children's home to visit Alexey and his younger sisters, Anastasia and Svetlana. But despite her compelling report the agency believes the denials of the adoptive mother and leaves the children in the abusive home. Knowing the horrible truth, the director faces one obstacle after another as she tried to find someone to protect the children from the unspeakable." --from page [4] of cover